Islam di Nusantara pada Abad ke-10 Masehi sebagaimana Tercermin dalam Tinggalan Budaya - Utomo, Bambang Budi (SUHUF, 2010)
Muslim merchants were active as traders from the seventh century. Several archipelago Hindu and Buddhist kingdoms established com-mercial and diplomatic connections with Middle Eastern Islamic rulers. Archaeological evidence pointing to this fact has been found at a shipwreck site in the Java Sea near Cirebon. Among the discovered trade goods were indications of Islam in the form of a stamp-mould with the inscription asma’ul husna. Although most of the Indonesian community follow Sunni teaching, in practice at this time in Sumatra and Java there are devotees of Syi’ah. Archaeological evidence points that Islam entered Southeast Asian archipelago from Persia via Gujarat, India. The religion was brought by merchants to Southeast Asia, especially to Indonesia and the Malay peninsula.